Discontinuous plasma flows in magnetohydrodynamics and in the physics of magnetic reconnection. (6th May 2015) - Ledentsov, N N; Somov, B V
Abstract: We review the current status of the theory of discontinuous magnetohydrodynamic (MHD) flows and its application to the physics of magnetic reconnection in astrophysical plasmas and in laboratory and numerical simulation studies. The emphasis is on the study of continuous transitions occurring between different types of discontinuities under gradual and continuous variation of the plasma flow parameters. The properties of the Syrovatskii reconnecting current sheet are described, and the possibility of the splitting of the current sheet into a system of MHD discontinuities is demonstrated. A simplified analytic model of magnetic reconnection is used to study the system of shock waves associated with the current sheet. With this system as an example, some implications of the conditions of continuous transitions and the possibility of additional plasma heating by a shock wave are considered.